VONNEGUT’S HUMANIST BELIEF AGAINST THE DEHUMANIZATION OF PEOPLE IN HIS THREE SELECTED SHORT STORIES - Rizka Khairina Johar (Vivid: Journal of Language and Literature, 2014)
In this study the author discusses several short story by American writer Kurt Vonnegut: "Harrison Bergeron", "Welcome to the Monkey House", and "Tomorrow and Tomorrow and Tomorrow". The three stories are in the genre of science fiction and tell the future state of the earth where there is a tremendous increase in the population. The concepts of repressive State Apparatus and Ideology State Apparatus by Althusser are used to analyze how the authorities control the public in order to maintain their positions as rulers. Kurt Vonnegut’s concept of Humanism is also explored in short stories. In his three short stories, Vonnegut reveals that people in power control people in such a way that it often unquestioned. The people in power in the stories establish inhumane rules with sanctions and therefore they are difficult to break. On the other hand the authorities influence the people by means of ideologies. These forms of controls are rejected by Kurt Vonnegut with brand of Humanism.Keywords: ideology, Humanism, dystopia, Vonnegut